Precise in-situ detection of adsorption kinetics based on fiber-optic sensing with a Y-shaped batch vessel. Issue 2 (31st August 2020) - Yang, Jingjing; Muhammad, Turghun; Pataer, Parezhati; Yang, Xiaoxia; Hoji, Amina; Zhang, Shubiao
Abstract: Batch adsorption is very important for characterization, screening and industrial applications. In this paper, a new Y-shaped absorption vessel with an incorporated membrane was designed and combined with a fiber-optic sensing spectrometer to realize in-situ automatic measurement of liquid-phase kinetics in batch adsorption. The main parameters which affect the mass transfer such as geometric sizes of the vessel and pore size of membranes were investigated. Compared with the adsorption bag and the traditional adsorption modes, the adsorption rate of the Y-shaped absorption vessel was in the first 5 hours of the adsorption of rutin on the macroporous resin by the in-situ method. Additionally, the adsorption rate of the Y-shaped adsorption vessel was closer to that of traditional adsorption. When the adsorption reached equilibrium, the equilibrium adsorption capacity of two modes were practically equal. The pseudo-second-order kinetic model accurately express the adsorption mechanism of rutin on the macroporous resin. The results show that the Y-shaped adsorption vessel improved the accuracy of the adsorption measurements and solve the problem of poor mass transfer caused by adsorption bag. This approach provides an in-situ, automatic and accurate method for batch processing and the screening of adsorbents.